The Early Schenkerians and the "Concept of Tonality" - John Koslovsky (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2016)
This essay investigates the role that a single expression played during the years when Schenker’s ideas began to disseminate en masse, the so-called “concept of tonality.” In particular, it examines how three key Schenker disciples—Oswald Jonas, Felix Salzer, and Adele Katz—used the expression to promote his/her own vision of Schenkerian analysis and pedagogy during the 1930s, 40s, and 50s. While considering the writings that gave birth to the expression, the essay also points to the common sources these early Schenkerians drew on in forming their narratives around Schenker, and it goes on to explore the divergent paths those narratives finally took. The essay then discusses two analyses, one by Jonas and one by Salzer, which demonstrate how Schenker’s core ideas and the newly-fashioned “concept of tonality” commingled in a single musical analysis. In the end, the essay argues that a subtle but crucial conceptual shift of Schenker’s ideas took place in the hands of his devotees early on, which had larger ramifications for the transmission of Schenkerian theory in later years.
Keywords: Schenker; tonality; Jonas; Katz; Salzer; Schenkerian theory; analysis